Electrospinning of polycaprolactone / bovine gelatin / bovine hydroxyapatite biomimetic composite nanofibers - Akalın, Güneş Ece. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2018., 2018)
In this study, Polycaprolactone (PCL) / Bovine Gelatin (GE) / Bovine Hydroxyapatite (BHA) biomimetic composite nanofiber scaffolds are manufactured for bone tissue regeneration applications by electrospinning. By controlling BHA concentration and GE concentration in the polymer solutions, the effects of the changes on the manufacturing process and on the nanofiber scaffolds are determined. The physical, morphological, chemical, mechanical and biological properties of PCL/GE/BHA electrospun nanofibers are produced by choosing a non-toxic solvent system. Physical properties of nanofiber scaffolds are recorded by measuring density, viscosity, surface tension and electrical conductivity. Morphological analyses of the nanofiber scaffolds are studied in SEM. Chemical bonds of the nanofiber scaffolds are analyzed by FTIR. Mechanical properties of the scaffolds are determined by using tensile test. Biological properties of the nanofiber scaffolds such as cell viability and attachment are tested by MTT Proliferation Assay and SEM Protocol for 24, 48 and 72 hours. The results of the morphological analyses (SEM) show that the fiber diameters of the nanofiber scaffolds are 119 ± 31 nm, 149 ± 44 nm, 306 ± 68 nm, 241 ± 55 nm and 384 ± 84 nm respectively. The experimental results show that ultimate tensile strength (UTS) of the nanofiber scaffolds are 9.1 ± 0.6 MPa, 15.7 ± 1.4 MPa, 15.8 ± 5.0 MPa, 30.9 ± 16.0 MPa and 15.8 ± 2.3 MPa. Cell attachment and spreading on the samples are observed in SEM. There is no cytotoxicity effect observed by MTT test for 72 hours. As a result of cell proliferation and viability analysis, there are biocompatible samples observed compatible with human osteoblast-like cells and mouse fibroblast cells with statistically significant results.
Keywords: Nanofibers.; Polycaprolactone.; Electrospinning.